A novel route to unsymmetrical disubstituted ureas and thioureas by HMPA catalyzed reductive alkylation with trichlorosilane. Issue 3 (2nd January 2020) - Ran, Xiaoyun; Long, Yan; Yang, Sheng; Peng, Changjiang; Zhang, Yuanyuan; Qian, Shan; Jiang, Zhenju; Zhang, Xiaomei; Yang, Lingling; Wang, Zhouyu; Yu, Xiaoqi
Abstract : A HMPA catalyzed reductive alkylation of ureas and thioureas with trichlorosilane under mild reaction conditions has been developed. Abstract : An HMPA catalyzed reductive alkylation of ureas and thioureas with trichlorosilane under mild reaction conditions has been developed. Both aldehydes and ketones could be used as efficient alkylation reagents in this method to obtain the desired products in moderate to high yields. A variety of di- and trisubsituted ureas and thioureas were easily prepared by this new reductive alkylation method. This protocol exhibits excellent functional group tolerance, chemoselectivity and practicality.